The Impact of Digital Transformation on Leadership from the Perspective of Financial Organizations' Performance and Growth Enhancement - Muzamil, Syed (Digital Repository of Theses - SSBM Geneva, 2024)
The increasing prevalence of digital technology in modern society has transformed the way organizations operate and has significantly impacted leadership roles. In the financial sector, the need to enhance performance and growth in the digital age requires leaders to adopt a "digital first" mindset, emphasizing the importance of technology in boosting creativity and productivity. Keeping abreast of technological advancements and comprehending the benefits and drawbacks of various digital tools and systems is critical for realizing the benefits of digital transformation. Leaders must be open to trying new things and taking calculated risks, while promoting a culture of agility and adaptation to respond to the ever-evolving digital landscape. However, the complexity and unpredictability of digital change require employees to be able to work well with ambiguity and uncertainty, making it essential to choose a leadership strategy that can advance the shift to a completely digital platform over the long term. This study aims to examine the impact of digital transformation on leadership style and its influence on financial organizations' performance and growth enhancement. It focuses on the various practices of digital transformation that impact financial organizations' performance and explores the role of a leader in adopting digital transformation to enhance performance. Additionally, the study examines the digital skills that CEOs should possess, the implications of digital transformation, and how different industries influence leadership style to respond to those influences. Understanding the impact of digital transformation on leadership in financial organizations will help leaders better position their organizations to thrive in the information era. Having a leadership strategy that is both effective and has lasting influence is crucial for a company to make the leap from a purely manual to a digital platform. Many executives are ill-equipped to handle this kind of change due to a lack of technical expertise. However, their participation is essential and demands flexibility (Kazim, 2019). There may be significant cost overruns and poor execution because of this shift. They must acquire new occupations and skills (Matt, Hess, and Benlian, 2015). To ensure that the digital transformation is a long-term success, leaders must have some influence and show their capacity to adopt a plan that does not restrict its success (Allio, 2015). Keywords: Digital Transformation, Leadership Style, Financial Organization